Value Engineering as a Specialty for Systems Engineering: Exploring Opportunities. Issue 1 (29th May 2019) - de Graaf, Robin; van der Linde, Gido; de Jong, Hein; Vogt, Berber
ABSTRACT: Value Engineering is a so‐called specialty engineering activity within Systems Engineering according to the INCOSE Systems Engineering Handbook [INCOSE, 2015], but what makes Value Engineering a 'specialty, ' and what can it offer Systems Engineers? In this article three Value Engineering concepts are described, which are the pillars of Value Engineering: 1) the definition of value, 2) the use of multi‐disciplinary workshops, and 3) the application of function diagramming with the FAST method. Each of these concepts is explained and ideas are put forward how to incorporate them in more commonly used Systems Engineering processes. Our findings show that Systems Engineering and Value Engineering are not mutually exclusive, but offer outstanding concepts to improve designers' goals. With this article, we hope to inspire the Systems Engineering and Value Engineering communities to further explore and experiment together.